Uncovering the lexical variation and change in Malaysian English: a corpus-driven analysis - Noraishah Gulnazir; Khazriyati Salehuddin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Malaysian English has been known to be influenced by local traits and characteristics as well as global influences and trends. Despite being traditionally based on the British English, Malaysians today seem to show increasing prominence in the use of American English due to its widespread dissemination on media. Thus, to investigate the influence of American English on Malaysian English, this study examined the usage of two American lexical items that emerged in American Twitter in 2013, namely, lit and on fleek, in Malaysian English. By using Twitter API Tools to obtain data, this research investigated 19,050 tweets totalling 203,482 tokens with lit and on fleek from the year 2013 until 2021 in Malaysian Twitter. Data were analysed through frequency distribution and concordance analysis via AntConc version 3.5.9. Additional tools such as Google Trends and Urban Dictionary were also utilised. The results reveal that lit and on fleek increased in usage in Malaysian Twitter in 2016 and 2017 respectively, two to three years after these lexical items first emerged in American English. Results also indicate that Malaysian Twitter users adopted these lexical items with the same precision in meaning as American English and incorporated them into Malaysian English. Aspects of semantic change or semantic drift are also revealed; these lexical items have transformed in terms of meaning and usage from its original form. This study supports the World System of Englishes theory by proving that lexical items from American English, as a hyper-central language, could spread to other varieties of English including Malaysian English. The research also demonstrates the concept of language mobility on social media, whereby lexical items from American Twitter could traverse to Malaysian Twitter. This study highlights the extent to which Malaysian English is influenced by American English and illuminates the dynamics of English language variation and change.